Combinations of plant essential oils and their major compositions inducing mortality and morphological abnormality of Aedes aegypti and Aedes albopictus - Mayura Soonwera; Tanapoom Moungthipmalai; Jirapon Aungtikun; Sirawut Sittichok (My University, 2022)
Extensive uses of synthetic insecticides to control mosquito's populations have induced the insects to develop resistance against them, rendering them ineffective today. Moreover, they cause serious impacts on human health and the ecosystem. Therefore, safe and effective natural alternatives are needed. This study evaluated the larvicidal and pupicidal activities of essential oils (EOs) from
Keywords: Aedes albopictus; Insecticide Resistance; Mosquito control; Insect Pest Control Strategies